2018
DOI: 10.3390/jcm7020011
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and Advances in Gestational Diabetes—An Update in the Era of Continuous Glucose Monitoring

Abstract: Diabetes in pregnancy, both preexisting type 1 or type 2 and gestational diabetes, is a highly prevalent condition, which has a great impact on maternal and fetal health, with short and long-term implications. Gestational Diabetes Mellitus (GDM) is a condition triggered by metabolic adaptation, which occurs during the second half of pregnancy. There is still a lot of controversy about GDM, from classification and diagnosis to treatment. Recently, there have been some advances in the field as well as recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 71 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…When the insulin secreted by the pancreas is not enough to control normal blood glucose levels, the blood glucose level rises, and the constant high levels of blood glucose contribute to the development of GDM (3). GDM is closely related to an increased frequency of fetal macrosomia, which may increase the incidence of development of cardiovascular disease, obesity, and diabetes for the descendant (4,5).…”
mentioning
confidence: 99%
“…When the insulin secreted by the pancreas is not enough to control normal blood glucose levels, the blood glucose level rises, and the constant high levels of blood glucose contribute to the development of GDM (3). GDM is closely related to an increased frequency of fetal macrosomia, which may increase the incidence of development of cardiovascular disease, obesity, and diabetes for the descendant (4,5).…”
mentioning
confidence: 99%
“…It is likely that an increase or even a stable HbA1c may represent worsening glycemic control during pregnancy, which may contribute to adverse outcomes. However, prior studies of early treatment for elevated HbA1c or gestational diabetes have not demonstrated improvement in perinatal outcomes associated with gestational diabetes 23,24 ; so while a stable or rising HbA1c may be associated with adverse outcomes, it is not known if early treatment will prevent these adverse outcomes. Of note, postpartum carbohydrate metabolism was not assessed given that the primary study was done in an antenatal population.…”
Section: Discussionmentioning
confidence: 98%
“…All pregnancies were screened for gestational diabetes between 24 and 28 weeks' gestation, using the clinical guidelines and standardized practices recommended by the American College of Obstetricians and Gynecologists. 22 The "oral glucose tolerance test" includes 100-g sugar. A diagnosis of gestational diabetes was made if the fasting blood glucose was ≥5.3 mmol/L, one-hour blood glucose ≥10.0 mmol/L, two-hour blood glucose ≥8.6 mmol/L, or three-hour blood glucose ≥7.8 mmol/L.…”
Section: Methodsmentioning
confidence: 99%